2018
DOI: 10.1097/corr.0000000000000539
|View full text |Cite
|
Sign up to set email alerts
|

Classifications in Brief: Sanders Classification of Intraarticular Fractures of the Calcaneus

Abstract: Clinical Orthopaedics and Related Research® neither advocates nor endorses the use of any treatment, drug, or device. Readers are encouraged to always seek additional information, including FDA approval status, of any drug or device before clinical use. Each author certifies that his institution approved the human protocol for this investigation, that all investigations were conducted in conformity with ethical principles of research, and that informed consent for participation in the study was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…In 1990, Crosby and Fitzgibbons [11] described a CT-based FCS, and according to the displacement of articular surface, it was divided into three types (Ⅰ-nondisplaced, Ⅱ-displaced, Ⅲ-comminuted). Besides, they were the first to correlated prognosis with the FCS [26]. In 1993, Sanders et al [12] developed a FCS from an assessment of 120 displaced calcaneal fractures, which was divided into four primary types (Ⅰ-Ⅳ)…”
Section: Discussionmentioning
confidence: 99%
“…In 1990, Crosby and Fitzgibbons [11] described a CT-based FCS, and according to the displacement of articular surface, it was divided into three types (Ⅰ-nondisplaced, Ⅱ-displaced, Ⅲ-comminuted). Besides, they were the first to correlated prognosis with the FCS [26]. In 1993, Sanders et al [12] developed a FCS from an assessment of 120 displaced calcaneal fractures, which was divided into four primary types (Ⅰ-Ⅳ)…”
Section: Discussionmentioning
confidence: 99%
“…Following CI, microglial activation occurs that leads to significantly increased aggregation of inflammatory cells and secretion of cytokines, with concurrent induction of acute neuroinflammation triggered by neuronal hypoxia within brain tissues. In various in vitro experiment models, inflammatory factors, such as TNF-α, IL-1β, and IL-6, have been shown to be associated with CI-induced brain injury ( Hovhannesyan and Hovhannisyan, 2019 ; Jimenez-Almonte et al, 2019 ). In accordance with the results of previous studies, the results of this study revealed that the levels of inflammatory factors, including TNF-α, IL-1β, and IL-6, were significantly reduced by TMGT treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In 1993, based on coronal and axis, CT images of the Sanders classification are the most used system for classifying ICFs [38], subdividing into four types, depending on the number of fractures and the position of fracture lines at the posterior calcaneal facet [5]. Despite its being widely used, the value of this classification is always disputed due to its limited reliability and validity [39]. This system does not consider fracture displacement in the sagittal or axial plane relative to the widest undersurface of the posterior talar articular surface and the pathological changes of calcaneal fractures.…”
Section: Discussionmentioning
confidence: 99%